2012
DOI: 10.1111/mmi.12053
|View full text |Cite
|
Sign up to set email alerts
|

PDZ domains of RseP are not essential for sequential cleavage of RseA or stress‐induced σE activation in vivo

Abstract: SummaryThe Escherichia coli s E extracytoplasmic stress response monitors and responds to folding stress in the cell envelope. A protease cascade directed at RseA, a membrane-spanning anti-s that inhibits s E activity, controls this critical signal-transduction system. Stress cues activate DegS to cleave RseA; a second cleavage by RseP releases RseA from the membrane, enabling its rapid degradation. Stress control of proteolysis requires that RseP cleavage is dependent on DegS cleavage. Recent in vitro and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 40 publications
3
47
0
Order By: Relevance
“…Recent structural data suggested that one function of the RseP PDZ domain is to bind the cleaved C terminus of the RseA anti-sigma factor generated by DegS (42), potentially providing a mechanism of coupling. However, recent in vivo examination of this model did not support this mechanism (27). Other recent data indicate that acid can activate RseA cleavage by RseP independent of DegS in S. typhimurium (41) and that LPS biosynthetic intermediates are a second signal for RseA degradation through binding RseB (43).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recent structural data suggested that one function of the RseP PDZ domain is to bind the cleaved C terminus of the RseA anti-sigma factor generated by DegS (42), potentially providing a mechanism of coupling. However, recent in vivo examination of this model did not support this mechanism (27). Other recent data indicate that acid can activate RseA cleavage by RseP independent of DegS in S. typhimurium (41) and that LPS biosynthetic intermediates are a second signal for RseA degradation through binding RseB (43).…”
Section: Discussionmentioning
confidence: 89%
“…The PDZ domain is a widely distributed protein-protein interaction motif that often organizes signaling complexes through binding C-terminal peptides (24). Deletion of the PDZ domain of E. coli RseP causes hyperactivation of the SigE pathway, DegS (S1P), independent cleavage of RseA, and insensitivity of SigE activation to RseB inhibition (20,21,23,27). However, no proteins have been identified that interact with the RseP-PDZ specifically, or S2P-PDZs more broadly, that may mediate these effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanehara et al (2003) suggested that glutamine rich regions in RseA (residues 162-169 and 190-200) suppress RseP-mediated proteolysis, as the removal of the motifs by DegS (the removal of RseA 149-216 ) can induce RseP cleavage. In other studies, residue V148 in RseA exposed by DegS cleavage was required as an RseP activation signal in an in vitro biochemical assay (Li et al, 2009), whereas the residue was not essential for RseA cleavage and sigmaE-dependent transcription in an in vivo assay (Hizukuri and Akiyama, 2012).…”
Section: Overall Signaling Pathway For Sigmae Releasementioning
confidence: 97%
“…RseB also controls DegS proteolysis of RseA by binding directly to the periplasmic domain of RseA [10]. DegS cleaved RseA is a substrate for RseP [1517], although the mechanism of coupling of these two proteolytic events remains controversial [18, 19]. Following RseP cleavage, the RseA/SigE complex is released to the cytoplasm where further degradation of RseA [20] releases SigE to associate with RNA polymerase to activate target promoters.…”
Section: Bacteriamentioning
confidence: 99%